Biomarkers of gut barrier failure in the ICU. Issue 2 (April 2016) - Piton, Gaël; Capellier, Gilles
Abstract : Purpose of review: Gut barrier failure is associated with bacterial translocation, systemic inflammation, and is presumed to be associated with the development of multiple organ dysfunction syndrome. As the gut barrier function is carried out by a monolayer of enterocytes, a minimum requirement is the integrity of the enterocytes, and controlled paracellular permeability between adjacent enterocytes. Many factors can cause critically ill patients to lose gut barrier function by a mechanism of enterocyte damage; for example, small bowel ischemia or hypoxia, sepsis, systemic inflammatory response syndrome, or absence of enteral feeding. Recent findings: Two enterocyte biomarkers may help the intensivist to identify enterocyte damage and dysfunction, namely plasma citrulline, a biomarker of functional enterocyte mass, and plasma or urinary intestinal fatty acid-binding protein, a marker of enterocyte damage. This review focuses on results obtained with these biomarkers in the context of critical care, in particular: prevalence of enterocyte biomarker abnormalities; mechanisms associated with enterocyte damage and dysfunction; link with systemic inflammation, bacterial translocation, and clinical intestinal dysfunction; prognostic value of enterocyte biomarkers. Lastly, we also review the limits of these biomarkers. Summary: Enterocyte biomarkers may help the intensivist to identify patients presenting with intestinal damage, and who are at risk of bacterial translocation and systemic inflammatory response syndrome, as well as those with decreased enterocyte function, at risk of malabsorption. Enterocyte biomarkers should be interpreted with caution in the critically ill and should be interpreted within the overall clinical context of the patient.